A Comparative Analysis of Foreign Direct Investment Attraction - Kuna, Andrew (Colloquium: The Political Science Journal of Boston College, 2019)
After the collapse of the Soviet Union over a dozen states had to learn how to adapt both their economies and their political systems. One crucial aspect of growing their new independent economies was attracting investment from other states. This paper analyzes the different strategies utilized for foreign direct investment by Czech Republic, Uzbekistan, and Moldova. The Czech Republic has been very open to foreign direct investment as they have joined the EU, and due to this openness it has had great success in attracting investment and growing their economy. Uzbekistan, a state plagued with corruption, has failed to reach the same high levels of investment resulting in a more poverty-stricken economy. Finally, Moldova has attempted to be more open than Uzbekistan throughpursuing investment strategies in the 21st century, but it too has been afflicted with heavylevels of corruption. Through identifying the internal problems of each of these nations it becomes more clear how they can garner future investments to help further develop their young economies.